Europe and global climate change politics, foreign policy and regional cooperation - Harris, Paul G.; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar Pub., 2007)
The core objective of this book is to better understand the role of foreign policy--the crossovers and interactions between domestic and international politics and policies--in efforts to preserve the environment and natural resources. Underlying this objective is the belief that it is not enough to analyze domestic or international political actors, institutions and processes by themselves. We need to understand the interactions among them, something that explicit thought about foreign policy can help us do.
pt. 1. Global climate change and policymaking in Europe -- pt. 2. The European Union and global climate change.
Includes bibliographical references and index.
Keywords: International relations -- Environmental aspects; Climatic changes -- Government policy -- Europe; Europe -- Foreign relations; Electronic books